The ecological importance of mixed-severity fires : nature's Phoenix - DellaSala, Dominick A., 1956-; Hanson, Chad T. (Amsterdam : Elsevier, 2015)
The Ecological Importance of High-Severity Fires, presents information on the current paradigm shift in the way people think about wildfire and ecosystems. While much of the current forest management in fire-adapted ecosystems, especially forests, is focused on fire prevention and suppression, little has been reported on the ecological role of fire, and nothing has been presented on the importance of high-severity fire with regards to the maintenance of native biodiversity and fire-dependent ecosystems and species. This text fills that void, providing a comprehensive reference for documenting and synthesizing fire's ecological role.
Biodiversity of mixed- and high-severity fires. Setting the stage for mixed- and high-severity fire -- Ecological and biodiversity benefits of megafires -- Using bird ecology to learn about the benefits of severe fire -- Mammals and mixed- and high-severity fire -- Stream-riparian ecosystems and mixed- and high-severity fire -- Bark beetles and high-severity fires in Rocky Mountain subalpine forests -- Global and regional perspectives on mixed- and high-severity fires. High-severity fires in chaparral: cognitive dissonance in the shrublands -- Regional case studies: Southeast Australia, Sub-Saharan Africa, Central Europe, and Boreal Canada -- Climage change: uncertainties, shifting baselines, and fire management -- Carbon dynamics of mixed- and high-severity wildfires: pyrogenic CO2 emissions, postfire carbon balance, and succession -- Managing mixed- and high-severity fires. In the aftermath of fire: logging an drelated actions degrade mixed- and high-severity burn areas -- The rising costs of wildfire suppression and the case for ecological fire use -- Flight of the phoenix: coexisting with mixed-severity fires.
Includes bibliographical references and index.
Keywords: Forest fires -- Prevention and control; Forest fires -- Environmental aspects; Forest ecology